Characterization of ZnO/nanofluid for improving heat transfer in thermal systems. (2022) - Sharma, Rajneesh; Chauhan, Prashant; Sharma, Amit Kumar; Katiyar, Atul; Singh, Hari Kumar; Rinawa, Moti Lal; Kumar, P. Manoj
Abstract: Nanofluids are currently regarded a new growing area of research with numerous advantages over conventional heat transport fluids in heat transfer applications. Because, nanofluids possess a better thermo-physical characteristics. Hence, they can perform better when compared to traditional working fluids. The thermo-physical characteristics of zinc oxide nanoparticles disbanded water (ZnO/water) nanofluid was evaluated in this study by altering the volume proportions of nano-ZnO particles and temperature experimentally. The volume proportion of ZnO/water nanofluids was adjusted from 0.01 to 0.2 in four different (0.01, 0.05, 0.1 and 0.2) fractions. Using a field emission scanning electron microscope, the surface properties of ZnO nanoparticles were investigated. The results evidenced that the absolute viscosity, thermal conductivity, and density of the water was augmented by 1.43%, 37.0%, and 1.57%, respectively through the diffusion of 0.2 vol% of nano-ZnO particles in water. In contrast, the specific heat of water was lessened by 2.7% with 0.2 vol% of nano-ZnO particles in water.